Headwater Flow Geochemistry of Mount Everest (Upper Dudh Koshi River, Nepal) - Chevallier, Pierre; Seidel, Jean-Luc; Taupin, Jean-Denis; Puschiasis, Ornella (Frontiers in Earth Science, 2020)
The aim of this work, conducted in the upper valley of the Khumbu on the southern part of Mount Everest, is to approach in parallel three topics: (i) the dynamics of the water geochemistry, major ions and trace elements; (ii) the stable water isotopes of precipitation and rivers; and (iii) the water uses by the inhabitants. As in most mountain environments, the Khumbu area is threatened by climate change, which impacts the cryosphere and consequently the people and the landscapes. Moreover, changes in water use are also related to new needs stemming from tourism, which strongly affect local livelihood. For the first two topics, new results are presented. They provide details on the global chemical quality of the river water and show how certain elements are seasonally influenced and how other elements allow us to distinguish the water origins within the study zone. Beside the use of stable isotopes to determine mainly the origin of the water flow in the rivers, the isotopic patterns confirm the double climatic influence of the westerly fluxes in the winter season and of the Asian monsoon in the summer season. Regarding water use, the study does not conclude on the potability of the water resource, because microbiologic and organic components have not been investigated; however it confirms that the chemical quality is good. In conclusion, we attempt to predict the future of the geochemistry patterns submitted to the double pressure of climate change and the surge in tourism.